Acute Care Surgery Handbook Volume 2 Common Gastrointestinal and Abdominal Emergencies - Di Saverio, Salomone; Catena, Fausto; Ansaloni, Luca; Coccolini, Federico; Velmahos, George (Springer International Publishing : Imprint: Springer, 2016)
This pocket manual is a practically oriented guide to abdominal and gastrointestinal emergencies in acute care surgery. It covers the most common injuries to the entire area, offering careful descriptions of diagnostic procedures, surgical techniques and non-operative management. The guide stems from collaboration with the World Society of Emergency Surgery (WSES) and aims to provide general surgeons, residents and trainees with a comprehensive and up-to-date overview of the most relevant operative techniques and with useful "tips and tricks" applicable in for their daily clinical practice. A second volume on other surgical emergencies, which also includes chapters on antibiotic management, nutrition and interventional radiology in acute care surgery, is also available.